PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SUBTEMA PELESTARIAN KEKAYAAN SUMBER DAYA ALAM DI INDONESIA - Maria Monica Situmorang; Yuyun Elizabeth Patras; Tatang Muhajang (STKIP Subang, 2023)
This research aims to determine the effect of the Problem Based Learning model on learning outcomes in the sub-theme of Preserving Natural Resource Wealth in Indonesia. This research was conducted at Sindang Barang 2 Public Elementary School Bogor City Classes IV –A and IV-B in May to even semester. Calculation of the N-Gain Problem Based Learning model is 71 with high criteria and completeness learning outcomes of 92%. The results of the hypothesis testing stated that Ho was rejected Ha was accepted. Because the calculation results tcount(26.92) > ttable (1.99210). Based on the results of the research, it means that there is an influence from the use of the Problem Based Learning Model on learning outcomes in the Preservation of Natural Resource Wealth in Indonesia subtheme. A very effective learning model for use in the Preservation of Natural Resource Wealth in Indonesia sub-theme is the Problem Based Learning model.